Does Minimalist Footwear Design Aid in Postural Stability and Fall Prevention in Ergonomics?. Issue 4 (October 2019) - Chander, Harish; Knight, Adam C.; Carruth, Daniel
The purpose of the article is to identify if novel footwear design could aid in postural stability and fall prevention in workplace. Footwear design has been reported to aid the task of maintaining postural stability or balancing in an erect stance while minimizing risk of falls. Minimalistic footwear that has design features such as low mass, lower heel height, and thin midsole can positively influence postural stability. Minimalistic military footwear has been shown to lower incidences of falls with efficient muscular effort. Occupational footwear that abides by safety standards with minimalistic features can help maintain postural stability and reduce falls.